The IMPORTANCE OF AFFIRMATIVE ACTION FOR STUDENTS WITH DISABLED IN INCLUSIVE EDUCATION - Andriani, Dian Sri (JIV-Jurnal Ilmiah Visi, 2022)
This paper aims to identify the importance of affirmative action for students with disabilities through the formulation of problems that arise in continuing education in inclusive schools in Indonesia. These problems were obtained from various previous studies so that this type of research is library research. Based on the results of a literature review, it is known that the problems encountered in the implementation of inclusive education occur on various sides, such as the very minimal number of accompanying teachers in inclusive schools, limited knowledge and skills of regular teachers, unavailability of facilities that support physical movement of students with disabilities, regulations that still discriminatory, and acceptance responses from non-disabled students, parents, and the school community as a whole. This has an impact on the emotional health of students with disabilities because they feel uncomfortable while at school and are not confident, both in the learning process and in building friendships with non-disabled students. As a result, many students with disabilities feel inferior and do not want to go to school, so it is necessary to take various affirmative actions that can motivate students with disabilities to attend school. Affirmative action will be right on target if it refers to the problems faced by students with disabilities, including those concerning physical, psychological, communication, social functions, and work skills. Through affirmative action, it is hoped that it can help foster self-confidence and comfort for students with disabilities.